Normal values ​​for sodium and potassium in the blood serum - Monge Cassinelli, Carlos Alberto (1952)
We have noted the normal values ​​of sodium and potassium in the serum of 50 normal subjects. The method employed was the flame photometer. Suggest the use of the technique and fast anaerobic whey separation in handling blood samples